Smart IoT-based temperature-controlled cooling system for solar panels using Arduino - Mula Sreenivasa Reddy; Kondragunta Rama Krishnaiah; Anjali Devi Gorla; Anantha Sravanthi Peddinti; Sanam Nagendram; Mohammad Najumunnisa; Bodapati Venkata Rajanna; Shaik Hasane Ahammad; Gongati Pandu Ranga Reddy (Institute of Advanced Engineering and Science, 2026)
The efficiency of solar photovoltaic panels declines significantly as their surface temperature increases beyond optimal levels. This paper presents a smart, temperature-controlled cooling system based on an Arduino UNO microcontroller to enhance solar panel performance by mitigating overheating. The system integrates a DS18B20 temperature sensor and a moisture sensor to monitor real-time environmental conditions. When the temperature exceeds a defined threshold, the Arduino activates a CPU fan and water pump to dissipate heat effectively. Experimental testing demonstrated an efficiency improvement of approximately 10% to 12% during peak solar conditions. A hysteresis logic-based system with autonomous control is used to control the amount of energy and water utilized, by only cooling when required. An LCD screen displays real-time information locally on-site, while an ESP8266 WiFi module sends information to a